STUDY ON CONSUMERS ACCEPTANCE OF LOMEK FISH SAUSAGE (Harpodon nehereus) FORTIFIED WITH CARROTS (Daucus carrota) FLOUR - Wahyu, Syafrudin; Desmelati, Desmelati; Suparmi, Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis study aims to determine the effect of fortification of carrot flour (Daucus corota) on lomek fish (harpodon nehereus) sausage towards consumer acceptance. The research method used was experimental, namely fortification of carrot flour on the lomek fish sausage. The research had two stages, namely the first stage making carrot flour and the second stage making lomek fish sausage with the addition of carrot flour. The research data were analyzed using a one-Factorial Completely Randomized Design (CRD). The parameters tested were organoleptic (appearance, texture, aroma, and taste), and proximate analysis (ash content, moisture content, and protein content). Research shows that the addition of carrot flour has a significant effect on consumer acceptance of lomek fish sausage with the addition of 10% carrot flour (S1) as the best treatment which is shown by the results of the organoleptic test in appearance values 7.17 (pure white color), aroma 7.01 (aroma lomek fish), taste 6.80 (savory, specific to lomek fish taste) and texture 6.35 (chewy, inelastic, and sticky texture). While the moisture, protein, and ash content was 72.18%, 11.70%, and 2.05% respectifely.Keywords: Carrot flour, lomek fish, sausage.